Ethnobotanical survey of homegardens in Agrovila in the municipality of Altamira, Pará, Brazil - Pereira, Sâmya Cristina Brazão; Jardim, Iselino Nogueira; Freitas, Alessandra Doce Dias; Paraense, Vinicius de Campos (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
Agroforestry systems have emerged as land use alternatives, capable of reconciling agricultural and forestry production, concomitantly with the conservation of natural resources. The objective of this work was to evaluate the homegardens present in an Agro-villa in the municipality of Altamira, Pará, Brazil, concerning its composition and floristic diversity, besides the uses of plants. The data were obtained from 26 homegardens established in the Xingu Princess agrovila by means of semi-structured interviews with key informants, selected by snowball technique. In order to analyze the use and relevance of the surveyed species, the Shannon-Wiener diversity index, Pielou equitability index and importance value (IVs) were calculated. A total of 117 plant species, belonging to 52 botanical families, were identified, highlighting: Fabaceae, Arecaceae, Anacardiaceae, most of them being used in family feeding. Among the species with the highest importance value to the interviewees, orange, coconut, mango, cacao, cupuaçu, lemon and açaí were highlighted. The food and medicine categories were the most important to the interviewees, which indicated concern with food safety and health for the rural community, respectively. The Shannon-Wiener and Pielou equitability indexes indicated moderate diversity and lower individual heterogeneity, respectively, per species in the homegardens of the Xingu Princesa agrovila.